On the Agony of Czech Slavic Paganism and the Representation of One's Own Funeral among Contemporary Czech Pagans - Maiello, Giuseppe (The pomegranate, 2017)
At the end of the 1990s in the Czech Republic a significant effort to revitalize the ethnic religion of the Slavs occurred. The emergence of this religious and cultural phenomenon was related in particular to two elements: to a nationalist organization and to a group of students of Slavic Studies in the College of Arts of Charles University in Prague. The study presents-in its first part-the activities of those students, their relationship with the Prague Slavic studies of this particular time and with the Indo-European ideology, which became dominant in the group that emerged after the collapse of the original Czech Rodná víra . In the second part of the study are presented the results of a field research into attitudes of Contemporary Czech pagans towards funeral and especiallytowards their own funeral.